2006
DOI: 10.1093/carcin/bgl233
|View full text |Cite
|
Sign up to set email alerts
|

Biological assays and genomic analysis reveal lipoic acid modulation of endothelial cell behavior and gene expression

Abstract: Lipoic acid (LA) is a sulfated antioxidant produced physiologically as a coenzyme of the pyruvate dehydrogenase complex; it is currently used for treatment of non-insulin-dependent diabetes to favor the cellular uptake of glucose. We have previously described the angiopreventive potential of molecules sharing common features with LA: N-acetyl cysteine, epigallocatechin-3-gallate and xanthohumol. To expand these studies, we have tested the capacity of LA to modulate angiogenesis in tumor growth using a Kaposi's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
2
19
1
1
Order By: Relevance
“…Biological assays and genomic analysis revealed that the antioxidant lipoic acid could modulate endothelial cell behavior and gene expression [35]. Lipoic acid can inhibit expression of ICAM-1 and VCAM-1 at the mRNA level in cultured human aortic endothelial cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Biological assays and genomic analysis revealed that the antioxidant lipoic acid could modulate endothelial cell behavior and gene expression [35]. Lipoic acid can inhibit expression of ICAM-1 and VCAM-1 at the mRNA level in cultured human aortic endothelial cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also suggested a role for redoxdependent processes in the control of HIF-1 because treatment with diamide or hydrogen peroxide results in loss of DNA binding activity (26). Although transfection of the small redox protein thioredoxin-1 increases HIF-1a protein and activity and VEGF expression (27), lipoic acid treatment, which strongly increases thioredoxin reductase 1 expression, has antiangiogenic activities both in vitro and in vivo (28).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…The primary antibodies used were a rabbit polyclonal anti-VEGF (Calbiochem, 1:50 dilution), and a polyclonal anti-asialo GM-1 (Wako Chemicals GmbH, 1:600 dilution). Staining with polyclonal anti-myeloperoxidase [14] and rat monoclonal CD31 [15] were as previously described. Sections were then lightly counter-stained with hematoxylin and mounted in glycergel.…”
Section: Histological Analysismentioning
confidence: 99%
“…Anti-asialo GM-1 positive NK cells were directly counted as the number of stained cells per highpower field. Vessels were identified and counted on the parental cell tumors with similar sizes having either pIRES (7) or IL-12 (5) expressing tumors controlaterally, using a previously described method [15] and the ImagePro-plus program to count vessel numbers and estimate average vessel area as well.…”
Section: Histological Analysismentioning
confidence: 99%